2021
DOI: 10.1096/fj.202100219r
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training ameliorates early diabetic kidney injury by regulating the H2S/SIRT1/p53 pathway

Abstract: Exercise training exerts protective effects against diabetic nephropathy. This study aimed to investigate whether exercise training could attenuate diabetic renal injury via regulating endogenous hydrogen sulfide (H2S) production. First, C57BL/6 mice were allocated into the control, diabetes, exercise, and diabetes + exercise groups. Diabetes was induced by intraperitoneal injection of streptozotocin (STZ). Treadmill exercise continued for four weeks. Second, mice was allocated into the control, diabetes, H2S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Better physical condition of exercised animals may lead to better hemodynamic and metabolic conditions and ultimately activation of molecular mechanisms of cell survival in kidney tissue [ 49 ]. SIRT1 expression was reduced in the AKI model [ 1 ], and it was shown that exercise reduces apoptosis by increasing SIRT1 expression [ 50 ]. SIRT1 is an evolutionary biological stress response that is associated with increased long-term function and survival of vital cell types [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Better physical condition of exercised animals may lead to better hemodynamic and metabolic conditions and ultimately activation of molecular mechanisms of cell survival in kidney tissue [ 49 ]. SIRT1 expression was reduced in the AKI model [ 1 ], and it was shown that exercise reduces apoptosis by increasing SIRT1 expression [ 50 ]. SIRT1 is an evolutionary biological stress response that is associated with increased long-term function and survival of vital cell types [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence that exosomes and associated miRNAs can impact renal tissues either directly or in synergy with other factors to shape the development and progression of DN [ 37 , 38 ]. Signal transduction pathways and associated regulatory networks are important areas of DN-related research that offer important insight into the etiological basis for this debilitating condition [ 39 41 ]. The development of drugs targeting DN-related signal transduction pathways may also hold great promise as an area for future research [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this NA-STZ diabetes animal model may also be used to evaluate any potential renoprotective effects of caloric restriction [ 142 , 143 , 144 ], intermittent caloric restriction [ 145 , 146 ], exercise [ 147 , 148 , 149 , 150 ], and ketone bodies [ 151 , 152 , 153 , 154 ], which all have been demonstrated to provide beneficial effects on the kidney in a variety of pathological conditions [ 155 , 156 ]. Indeed, the underlying mechanisms of renoprotection conferred by these approaches in this non-obese type 2 diabetes model remain to be comprehensively elucidated.…”
Section: Redox-related Mechanisms That Remain To Be Elucidated In Thi...mentioning
confidence: 99%